THE IMPORTANCE OF SPORTS PSYCHOLOGY IN ATHLETES' PERFORMANCE. (Universal International Scientific Journal, 2026)
This article analyzes the widespread problem of sports psychology among students and the pedagogical and psychological possibilities of using various skills and techniques to reduce it. It also discusses the factors that cause sports psychology, its impact on the educational process, and ways to eliminate this problem using modern sports psychology, as well as the importance of sports psychology in increasing motivation in the educational process, developing effective time management skills, and developing independent learning.
Keywords: Sports; psychology; science